A novel LaGa0.65Mg0.15Ni0.20O3–δ perovskite catalyst with high performance for the partial oxidation of methane to syngas - Meng, B.; Zhang, H.; Zhao, Z.; Wang, X.; Jin, Y.; Liu, Shaomin (Elsevier, 2014)
A novel perovskite catalyst with the composition of LaGa0.65Mg0.15Ni0.20O3–δ (LGMN) is synthesized by the sol–gel combustion technique. The nanostructure catalyst has been examined for the partial oxidation of methane (POM) into syngas. A variety of characterizations including XRD, BET, SEM and TG–DTA were applied to determine the crystalline structure of the formed nanosized particles. The syngas selectivity over the catalyst may reach up to 100% with the methane conversions larger than 81% at 900 °C and 55 mL min−1 g−1 feed velocity. XRD and thermal analysis reveals that the LGMN powder has maintained the perovskite structure very well after 210 h POM reaction signaling its high chemical stability.